Human Consciousness: Where Is It From and What Is It for - Kotchoubey, Boris (Frontiers in Psychology, 2018)
Consciousness is not a process in the brain but a kind of behavior that, of course, is controlled by the brain like any other behavior. Human consciousness emerges on the interface between three components of animal behavior: communication, play, and the use of tools. All three do not exclusively distinguish our close relatives, i.e., primates, but are broadly presented among various species of mammals, birds, and even cephalopods. These three components interact on the basis of anticipatory behavioral control, which is common for all complex forms of animal life. The interaction between communication and play yields symbolic games, the most important of which being language; the interaction between symbols and tools results in human praxis. Taken together, this gives rise to a mechanism that allows a creature, instead of performing controlling actions overtly, to play forward the corresponding behavioural options in a “second reality” of objectively (by means of tools) grounded symbolic systems. The theory possesses the following properties: 1. It is explicitly anti-reductionistic and anti-eliminativistic, and yet, human consciousness is considered as a purely natural (biological) phenomenon. 2. It avoids epiphenomenalism and indicates in which conditions human consciousness has evolutionary advantages, and in which it may even be disadvantageous. 3. It allows to easily explain the most typical features of consciousness, such as objectivity, seriality and limited resources, the relationship between consciousness and explicit memory, the feeling of conscious agency, etc. The relationships between the present model and other, traditional and modern, theories of consciousness, from substance dualism to Dennett’s reductionism and Baars’ Common Workspace model, remains a topic of a following analysis.